Green Ports - Zis, Thalis (My University, 2019)
Sustainable shipping involves not only ships but ports as their extension. This chapter examines the issues associated with a green port operation. These include technologies such as cold ironing; market-based practices such as differentiated fairway dues, speed reduction, and noise and dust abatement; and others. The legislative framework in various countries is explained, and various environmental scorecards are discussed. This chapter starts with a brief review on recent academic research in the field of environmental management of ports and presents the status quo in leading ports around the world. The chapter emphasizes on the implementation of speed reduction programmes near the port, the use of cold ironing at berth, and the effects of fuel quality regulation, considering the perspectives of the port authority and the ship operator. The emerging environmental and economic trade-offs are discussed. The aim of this chapter is to be a starting point for researchers seeking to work on green ports. Insights of this chapter may also be useful for stakeholders seeking to select the best emissions reduction option depending on their unique characteristics.